A facile and general acid-catalyzed deuteration at methyl groups of N-heteroarylmethanes. Issue 12 (7th March 2017) - Liu, Min; Chen, Xue; Chen, Tieqiao; Yin, Shuang-Feng
Abstract : A general acid-catalyzed deuteration at the methyl group of N -heteroarylmethanes was achieved, which could be conducted at a 500 mmol-scale, showing its good potential for use in large-scale synthesis. Abstract : A facile and general Brønsted acid-catalyzed deuteration at the methyl group of N -heteroarylmethanes was achieved through a dearomatic enamine intermediate under relatively mild reaction conditions. Both 2-methyl and 4-methyl groups in quinolines were deuterated with high deuterium incorporation. Pyridines, benzo[ d ]thiazoles, indoles and imines including these clinical drugs were also deuterated efficiently at the methyl groups. This reaction could be conducted on a large scale (500 mmol), showing its good potential for use in large-scale synthesis.